2022
DOI: 10.1177/03635465211068109
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Outcomes After Hip Arthroscopy in Patients With Femoroacetabular Impingement and Borderline Dysplasia

Abstract: Background: The role of hip arthroscopy in the treatment of patients with borderline hip dysplasia is controversial and evolving. Purpose: To evaluate outcomes at a minimum 10-year follow-up in patients who underwent hip arthroscopy for femoroacetabular impingement in a hip with borderline dysplasia. Study Design: Case series; Level of evidence, 4. Methods: All hips that underwent labral repair between June 2006 and March 2009 for femoroacetabular impingement with borderline dysplasia were included if they had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…The authors noted that “being physically active” and female sex were independent predictors of achieving the MCID, while running, female sex, and a larger preoperative LCEA were predictors of achieving the PASS. Beals et al 1 reported a case series without a control group of 10-year data in patients with BD, with rates of achieving the MCID >80% for the HOS-ADL and HOS-SSS in those who did not convert to THA, indicating that a subset of patients fared well with isolated hip arthroscopic surgery, most likely those with a primary diagnosis of impingement without osteoarthritis. They noted rates of conversion to THA of 13% and 21% at 5 and 10 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors noted that “being physically active” and female sex were independent predictors of achieving the MCID, while running, female sex, and a larger preoperative LCEA were predictors of achieving the PASS. Beals et al 1 reported a case series without a control group of 10-year data in patients with BD, with rates of achieving the MCID >80% for the HOS-ADL and HOS-SSS in those who did not convert to THA, indicating that a subset of patients fared well with isolated hip arthroscopic surgery, most likely those with a primary diagnosis of impingement without osteoarthritis. They noted rates of conversion to THA of 13% and 21% at 5 and 10 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For patients who did not convert to THA in that study, MCID rates of >80% for the Hip Outcome Score–Activities of Daily Living (HOS-ADL) and Hip Outcome Score–Sports-Specific Subscale (HOS-SSS) were achieved, and the authors indicated that patient selection is critical to success in the BD cohort. 1…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study examining 10-year outcomes in patients with borderline dysplasia, with survivorship defined as the avoidance of THR, Beals et al 1 reported a 5-year survival rate of 87% and 10-year survival rate of 79%. In the current study, a survival rate of 97% was observed at 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Longer term data for the MCID in dysplasia cohorts are lacking. While Beals and colleagues 1 reported MCID rates in patients with dysplasia, they did not include a control group, and thus, it was not possible to determine whether MCID achievement rates differ between dysplasia and FAI control groups with a longer follow-up. There was no difference observed in MCID achievement rates between borderline and severe dysplasia cases in this study, indicating similar clinically relevant improvements after corrective FAI surgery.…”
Section: Discussionmentioning
confidence: 99%